Using Internship Management System to Improve the Relationship between Internship Seekers, Employers and Educational Institutions - Hyrmet Mydyti; Arbana Kadriu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
This paper aims to research demands and practices on internships. The internship management system (IMS) is a fundamental fragment of communication between students, educational institutions and businesses (S-B-A) and is an influential tool to improve the digitization of processes related to internships. The Internship Management System (IMS) will ease many processes between the counterparts. Internships will ease the process of discovering talents fitting the internal culture of the companies and increasing the companies' productivity. Moreover, the internships will assist educational institutions being market-oriented by making students before their graduation to be better informed with the requests of the market and being aware of their skills and abilities. In this paper, we have given different perspectives and approaches on practices of internships, design patterns and frameworks on reinforcing the communication between the three above-mentioned pillars (S-B-A). Questionnaire surveys have been used as a methodology for conducting this research. Businesses have been the subject of the study and the obtained information provides a better observation of the study.
Keywords: C88; 330; Internship; Design Pattern; Framework; Technology; MVC; Stata; MySQL